Beyond Clinical Outcomes: Exploring the Psychosocial and Physical Dimensions of Quality of Life in Tuberculosis Patients Receiving Outpatient Care - Yuliyanti, Sri (HM Publisher, 2024)
Tuberculosis (TB) remains a global health challenge, with significant implications for patients' quality of life (QoL). While clinical outcomes are crucial, understanding the broader impact of TB on patients' psychosocial and physical well-being is essential for comprehensive care. This study aimed to explore the multifaceted nature of QoL in TB patients receiving outpatient treatment, delving into both psychosocial and physical dimensions. A cross-sectional study was conducted among TB patients attending outpatient clinics at a tertiary care hospital. The Short Form-36 (SF-36) questionnaire was used to assess QoL across eight domains: physical functioning, role limitations due to physical health, bodily pain, general health perceptions, vitality, social functioning, role limitations due to emotional problems, and mental health. Sociodemographic and clinical data were also collected. Descriptive statistics, correlation analysis, and regression models were employed to analyze the data. The study included 150 TB patients (mean age: 42.3 years, 58% male). The overall QoL was significantly impaired, with the mental health domain showing the most pronounced impact. Factors associated with poorer QoL included female gender, lower socioeconomic status, presence of comorbidities, and longer duration of TB treatment. Notably, social support emerged as a significant predictor of better QoL across multiple domains. TB significantly affects patients' QoL, extending beyond physical symptoms to encompass psychosocial well-being. Addressing mental health concerns, providing social support, and considering socioeconomic factors are crucial components of holistic TB care. The findings underscore the need for interventions that go beyond clinical management to enhance the overall QoL of TB patients.